2012
DOI: 10.1039/c2ra20346d
|View full text |Cite
|
Sign up to set email alerts
|

Coal fly ash supported Co3O4 catalysts for phenol degradation using peroxymonosulfate

Abstract: Several fly ash (FA) samples derived from Australian (FA-WA) and Brazilian coals (FA-JL and FA-CH) were used as supports to prepare Co oxide (Co)-based catalysts. These Co/FA catalysts were tested in peroxymonosulfate activation for sulphate radical generation and phenol degradation in aqueous solution. The physicochemical properties of FA supports and Co/FA catalysts were characterised by N 2 adsorption, X-ray diffraction (XRD), scanning electron microscopy coupling with energy dispersive spectroscopy (SEM-ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…Phenol degradation was 68.3%, 57.8%, and 48.9% after 180 mins using at 0.5, 2, and 3 mg/L initial phenol concentration. Muhammad et al [28] reported that a higher phenol concentration often leads to low phenol degradation efficiency which is in agreement with trend obtained in this study. The present study is consistent with that of Paul et al [29] who reported that g-C3N4 photocatalyst at various loading significantly influences the photodegradation of methylene blue in contaminated water.…”
Section: Effect Of Initial Phenol Concentrationsupporting
confidence: 93%
“…Phenol degradation was 68.3%, 57.8%, and 48.9% after 180 mins using at 0.5, 2, and 3 mg/L initial phenol concentration. Muhammad et al [28] reported that a higher phenol concentration often leads to low phenol degradation efficiency which is in agreement with trend obtained in this study. The present study is consistent with that of Paul et al [29] who reported that g-C3N4 photocatalyst at various loading significantly influences the photodegradation of methylene blue in contaminated water.…”
Section: Effect Of Initial Phenol Concentrationsupporting
confidence: 93%
“…As shown in Figure , the three tangent lines are extrapolated to get E g1 (Co 3 O 4 , 1.84 eV), E g2 (Co 3 O 4 , 2.89 eV) and E g3 (ZnO, 3.58 eV) values of ZnO/Co 3 O 4 microsphere. The bandgap energy of 1.84 eV is the charge transfer from O 2− to Co 2+ , while 2.89 eV is derived from the charge transfer from O 2− to Co 3+ . It can be seen that doping Co 3 O 4 broadens the photoresponse range of ZnO, resulting in enhanced photodegradation efficiency via electron transfer.…”
Section: Resultsmentioning
confidence: 99%
“…26 Coal y ash (FA) contains many similar catalytic "ingredients" to such clays, including Al 2 O 3 , Fe 2 O 3 , K 2 O, CaO, MgO, Na 2 O, oen supported on an SiO 2 matrix. 42 Over 100 million tons of FA, the result of coal-burning in power stations and other industrial sources, 43 are produced annually. Much of this FA is deposited in containment ponds, posing health, safety and environmental risks.…”
Section: Introductionmentioning
confidence: 99%